2016
DOI: 10.1002/jmor.20610
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation among the inner ears of extinct and extant baleen whales (Cetacea: Mysticeti)

Abstract: Living mysticetes (baleen whales) and odontocetes (toothed whales) differ significantly in auditory function in that toothed whales are sensitive to high-frequency and ultrasonic sound vibrations and mysticetes to low-frequency and infrasonic noises. Our knowledge of the evolution and phylogeny of cetaceans, and mysticetes in particular, is at a point at which we can explore morphological and physiological changes within the baleen whale inner ear. Traditional comparative anatomy and landmark-based 3D-geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 68 publications
(112 reference statements)
5
56
1
Order By: Relevance
“…Therefore, within cetaceans, infrasonic hearing can be regarded as a purely mysticete trait, and ultrasonic hearing as an odontocete trait. Also, Mourlam and Orliac (2017) concluded that infrasonic and ultrasonic hearing evolved after the emergence of fully aquatic whales and within Neoceti, which contrasts with previous results of infrasonic sensitivity in basilosaurids (Ekdale, 2016;Park et al, 2017). However, no archaeocetes were included in our study, and a more detailed interpretation would be merely speculative based on our data.…”
Section: Occurrence Of Very Low-frequency and Infrasonic Hearingcontrasting
confidence: 86%
“…Therefore, within cetaceans, infrasonic hearing can be regarded as a purely mysticete trait, and ultrasonic hearing as an odontocete trait. Also, Mourlam and Orliac (2017) concluded that infrasonic and ultrasonic hearing evolved after the emergence of fully aquatic whales and within Neoceti, which contrasts with previous results of infrasonic sensitivity in basilosaurids (Ekdale, 2016;Park et al, 2017). However, no archaeocetes were included in our study, and a more detailed interpretation would be merely speculative based on our data.…”
Section: Occurrence Of Very Low-frequency and Infrasonic Hearingcontrasting
confidence: 86%
“…Further indicative of low-frequency hearing are the higher number of turns in archaeocete and toothed mysticete cochleae (more than 2), as well as the large amount of overlap of the basal turn by the apical turn(s). Additionally, preliminary results of a quantitative shape analysis of cetacean cochleae by Ekdale [4] indicate that Zygorhiza and an indeterminate species of toothed mysticete (ChM PV5720) plot within the cochlear morphospace of mysticetes. A final point to note is that virtually all studies to date [3][4][5][6]9,[18][19][20][21][22] on the diversity/evolution of cetacean inner ear anatomy have sampled different taxa/specimens for scanning/analyses under differing protocols.…”
Section: (B) Hearing Across the Archaeocete -Mysticete Transitionmentioning
confidence: 99%
“…Although it is debated whether the earliest cetaceans (archaeocetes) were low-or high-frequency specialists [3][4][5], archaic odontocetes have been shown to use high-frequency echolocation [5 -7]. However, no descriptions of the cochlear anatomy of early mysticetes have been published, which included the critical transition from predation using teeth to filtering with baleen [8].…”
Section: Introductionmentioning
confidence: 99%
“…In monotremes, the cochlear apex containing the lagena is coiled and enlarged (Schultz et al, ), while gondwanatherian mammals show a short tapering cochlear canal with a slightly curved apex (Hoffmann, O'Connor, Kirk, Wible, & Krause, ). Therian mammals (marsupials and placentals) show at least one full turn but can have more than three turns (e.g., 3.25 in domestic cats [Schellhorn, ], or 3.3 in whales [Ekdale, ]). Furthermore, the shape of the cochlear is phylogenetically informative in whales (toothless: Ekdale, ; toothed: Costeur et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therian mammals (marsupials and placentals) show at least one full turn but can have more than three turns (e.g., 3.25 in domestic cats [Schellhorn, ], or 3.3 in whales [Ekdale, ]). Furthermore, the shape of the cochlear is phylogenetically informative in whales (toothless: Ekdale, ; toothed: Costeur et al, ).…”
Section: Introductionmentioning
confidence: 99%